An algorithm for computing the Hilbert–Samuel multiplicities and reductions of zero-dimensional ideals of Cohen–Macaulay local rings. (January 2020) - Shibuta, Takafumi; Tajima, Shinichi
Abstract: In this paper, we present an algorithm for computing the minimal reductions of m -primary ideals of Cohen–Macaulay local rings. Using this algorithm, we are able to compute the Hilbert–Samuel multiplicities and solve the membership problem for the integral closure of m -primary ideals.